Documents about the story of the Hungarian-Libyan diplomatic connections - Szilágyi, Péter (Études sur la Région Méditerranéenne, 2006)
The aim of this study is to introduce sources that came to existence during the official and non-official negotiations between Hungary and Libya started at the end of the 1950s. In the mirror of these we can get an objective picture about the steps of the Hungarian diplomacy towards the Libyan partner. This work used mainly those diplomatic documents from the National Archives of Hungary that have reference to Libya. Most of the documents are from the State Department and from the embassy of the People's Republic of Hungary in Cairo. Furthermore, some documents are from the Washington, Moscow and Belgrade embassies of the People's Republic of Hungary1.